Sistem Informasi Kepegawaian Pengadilan Negeri Takengon - Wati, Rayu; Frasiska, Widiya (Universitas Gajah Putih, 2025)
This study aims to develop a web-based Employee Information System at the Takengon District Court to improve the efficiency of employee data management. The system is designed to address various challenges in personnel management, which was previously conducted manually, making it prone to errors and delays in retrieving information. Using the Waterfall software development methodology, the system is systematically built through the stages of requirements analysis, design, implementation, and testing. The developed system enables faster and more accurate processing and recording of employee work histories, while also facilitating employee data retrieval. The web-based implementation supports transparency and accessibility of information for all employees. The research findings indicate that this system enhances efficiency in employee data recording, though further development is required to improve features and data security.